2007
DOI: 10.1016/j.ddmec.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related lung disorders

Abstract: Highly active antiretroviral therapy (HAART) has dramatically altered the spectrum of morbidity and mortality in HIV-infected patients. This has been attributed to improvements in the lung microenvironment leading to enhanced pulmonary immunity, either by preventing the progressive loss of immune function or by actually promoting immune restoration. However, these changes have been accompanied by the recognition of new pulmonary complications in HIV-infected subjects, especially those associated with immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…The source of antigen in IRIS may be of infectious or non-infectious origin. HIV proteins have not been excluded as targets in IRIS, though the low HIV levels observed in the alveolar space following HAART argues against this possibility [219]. However, cases of LIP and IP following HAART have been described as part of IRIS where no obvious infectious agent was found [220,221].…”
Section: Lung Diseasementioning
confidence: 96%
See 1 more Smart Citation
“…The source of antigen in IRIS may be of infectious or non-infectious origin. HIV proteins have not been excluded as targets in IRIS, though the low HIV levels observed in the alveolar space following HAART argues against this possibility [219]. However, cases of LIP and IP following HAART have been described as part of IRIS where no obvious infectious agent was found [220,221].…”
Section: Lung Diseasementioning
confidence: 96%
“…Similarly, in patients with LIP, HAART induces clinical improvement accompanied by a large reduction in virus load [218]. However, HAART is associated with new pulmonary complications such as immune reconstitution inflammatory syndrome (IRIS) and chronic obstructive pulmonary disease in some patients [219]. IRIS in particular is observed in up to 25% of patients.…”
Section: Lung Diseasementioning
confidence: 99%
“…Numerous studies have demonstrated persistence of chronic lung inflammation even in subjects infected with HIV on HAART (32)(33)(34). It is tempting to speculate that this chronic inflammation may contribute to lung complications seen in the HAART era, which have moved away from classic opportunistic infections toward more chronic lung diseases, such as chronic obstructive pulmonary disease, pulmonary hypertension, and lung cancer (35).…”
Section: Original Articlementioning
confidence: 99%
“…Continuous ART is associated with a decreased risk overall of AIDS and non-AIDS events (37), and ART has been suggested to have a protective effect on pulmonary function (38). Within the alveolar space, ART also decreases pulmonary HIV viral load and decreases nonspecific pulmonary inflammation (39,40). However, current data on the impact of ART on lung function and chronic pulmonary disease are conflicting, because another study has found that airflow obstruction was more likely in patients on ART (41).…”
Section: Table 2 Incidence Rate Ratio For the Association Of Hiv Infmentioning
confidence: 99%